2016
DOI: 10.1159/000446724
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Age and Numerical Chromosome Abnormalities in Human Spermatozoa

Abstract: This study explores the relationship between numerical chromosome abnormalities in sperm and age in healthy men. We performed FISH in the spermatozoa of 10 donors from the general population: 5 men younger than 40 years of age and 5 fertile men older than 60 years of age. For each chromosome, 1,000 sperm nuclei were analyzed, with a total of 15,000 sperm nuclei for each donor. We used a single sperm sample per donor, thus minimizing intra-donor variability and optimizing consistent analysis. FISH with a TelVys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…To date, a handful of studies have examined whether advancing paternal age contributes to sperm aneuploidy. The majority of these provide little evidence to support a correlation between advancing paternal age and increased levels of sperm aneuploidy (Fonseka & Griffin 2011, Andreescu et al 2016, Donate et al 2016. There may be a very small effect for a handful of chromosomes in much later years, typically decades after what would traditionally be considered 'reproductive age' (Griffin et al 1995, Fonseka & Griffin 2011, Garcia- Ferreyra et al 2018).…”
Section: Sperm Aneuploidy Levels In Men With Proven Fertility or Withmentioning
confidence: 99%
“…To date, a handful of studies have examined whether advancing paternal age contributes to sperm aneuploidy. The majority of these provide little evidence to support a correlation between advancing paternal age and increased levels of sperm aneuploidy (Fonseka & Griffin 2011, Andreescu et al 2016, Donate et al 2016. There may be a very small effect for a handful of chromosomes in much later years, typically decades after what would traditionally be considered 'reproductive age' (Griffin et al 1995, Fonseka & Griffin 2011, Garcia- Ferreyra et al 2018).…”
Section: Sperm Aneuploidy Levels In Men With Proven Fertility or Withmentioning
confidence: 99%
“…Abnormal chromosomal segregation occurring during meiosis can lead to aneuploidy in both male and female gametes by deleting or including an extra copy of chromosomes (Hassold and Hunt 2001;Lamb et al 2005). Nevertheless, there is a difference in frequency of aneuploidy observed in spermatozoa (~4.5%) and oocytes (~20%) (Donate et al 2016). The difference in the incidence of aneuploidy among the male and female gametes can be attributed to the earlier completion of meiosis in the spermatozoa than its counterpart, and that it is equipped with more effective check-points before fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…In a study evaluating numeric chromosomal abnormalities in sperm of semen donors, no differences were observed in older men (aged 60-74, mean age 66.4 years) when compared to younger counterparts (aged 23-37, mean age 27.8 years). 55 In other study comparing sperm aneuploidy rates between infertile men with oligoasthenoteratozoospermia (OAT) and fertile men, Andreescu et al did not find any differences in aneuploidy rates with increasing paternal age. 56 The authors showed, however, that sperm from OAT patients exhibited higher rates of aneuploidy than fertile men, with increased nullisomy or disomy of chromosomes 13, 18, 21, X, and Y.…”
Section: Impact Of Advanced Paternal Age On Sperm Parametersmentioning
confidence: 95%